Diagnostic and management considerations in incidental common peroneal intraneural haemangioma. (August 2020) - Jo, Therese; Newey, Allison; Brazier, David; Biggs, Michael
Highlights: We describe a case of an incidentally diagnosed paediatric intraneural haemangioma. This is the third case to be reported in the common peroneal nerve. Intraneural haemangiomas often have non-specific features on imaging. This case demonstrated avid enhancement and peri-lesional oedema on MRI. Diagnosis was made on biopsy and the patient remains stable with observation. Abstract: Intraneural haemangiomas are rare tumours that can affect peripheral nerves. We describe a case of a 10-year-old female with an incidental finding of a common peroneal nerve lesion following knee injury. MRI demonstrated avid heterogeneous enhancement and peri-lesional oedema, and an open biopsy was performed revealing haemangioma on histopathological analysis. The patient was managed with observation and remains intact at 24-month follow-up.